Effect of the Heterogeneous Catalytic Activity of Electrodes for Mixed Potential Sensors. Issue 16 (1st January 2018) - Ritter, Thomas; Lattus, Julia; Hagen, Gunter; Moos, Ralf
Abstract : The concept of mixed potential sensors bases on the principle that competing reactions form a mixed electrode potential. The exchange of charge carriers takes place at the TPB. However, it is also assumed that heterogeneously catalyzed gas phase reactions reduce the analyte concentration locally. Since this already occurs before the analyte reaches the TPB, the actually detected concentration is not equal to the dosed concentration. This mechanism is investigated in this work using different electrode configurations. Platinum electrodes designed as full-circles are compared with mesh electrodes. The full-circle electrode shows reduced sensitivity, since the high precious metal content probably catalyzes the gas phase reaction more strongly. This was also confirmed by an electrochemical characterization using polarization curves. The sensitivity of the electrode also increases due to higher sintering temperatures and thus reduced porosity, which influences the area available for heterogeneous catalysis. When gold is used as electrode, this mechanism can hardly be observed, since Au shows low catalytic activity towards the oxidation of the used propene. It is shown how heterogeneous catalytic activity of electrodes affects the sensor signal and to what extent a deviation from the conventionally used mixed potential theory is expected at low analyte concentrations.